Recent Developments in India’s Balance of Payments: An Analysis: A comprehensive analysis of India's recent Balance of Payments developments (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This article seeks to analyse the recent developments in India’s Balance of Payments as well as India’s BoP position during the period from. 2008-09 to 2014-15. It also tries to explain the reasons behind such changes in India’s BOP. During 2008-09 global financial crisis had put BoP again in stress and stood at US -20080 million of deficit, the CAD ratio to GDP was 2.3. During 2011-12 current account of BOP has started to widen in dangerous level and reached to US 78155 million and ratio to the GDP was 4.2. The India’s merchandise trade was also increased, and its share to the GDP reached to 10.3. Again during 2011-12 and 2012-13 India’s BoP position was not favourable due to the dangerous level of increase in CAD and merchandise trade balance, during 2011-12 BoP stood at US 78155 million and ratio to the GDP was 4.2, in 2012-13 small surplus of US 3826 million was recorded in India’s Balance of Payments position but merchandise trade deficit has raised to 10.7 to the GDP. In 2014-15 India’s BOP position has been improved compared to the previous year.